Proteome of biofilm produced by a S. pseudintermedius strain - Magalhães, Ilídio Miguel Teixeira (2018)
Staphylococcus pseudintermedius is an opportunistic pathogenic bacterium responsible for most skin and post-surgical infections in dogs. The number of bacterial strains resistant to β-lactam antibiotics is increasing and are the major challenges now faced by veterinary medicine. Bacteria that produce biofilm are more resistant to treatment and thus, the production of this structure is already considered a virulence factor. In a biofilm, bacteria are embedded in a matrix of extracellular polymeric substances (EPS) some of which are proteins. With the objective to know more of this array element, the characterization of the biofilm matrix proteome (BMP) from a highly virulent S. pseudintermedius strain isolated from a dog with severe pyoderma was performed. Biofilm was developed by culturing the S. pseudintermedius strain 5819/10 in specific media. The biofilm matrix was then be separated from bacterial cells and evaluated for their protein content and complexity. Finally, the proteome was separated by 1D electrophoresis and characterized by nanoLC-ESI-Q-TOF and analysed using bioinformatics tools. The BMP of strain S. pseudintermedius 5819/10 consisted in a diverse group of proteins, where 63% of the proteins could be related to either the extracellular region or the plasma membrane, as protein complexes, and most of them had functions essential to cell survival. However, it was not possible to establish a clear relation between them and biofilm formation. Proteins known to be involved in biofilm formation consisted mostly of regulator factors of biofilm formation as well as virulence factors of-mainly-bacterial cell adhesion and host colonization. The prevalence of adhesins and the almost total absence of proteins involved in EPS synthesis pointed to a biofilm matrix where cells are directly or indirectly closely glued together to each other.